A Probiotic Spore‐Based Oral Autonomous Nanoparticles Generator for Cancer Therapy. Issue 43 (6th September 2019) - Song, Qingling; Zheng, Cuixia; Jia, Jiajia; Zhao, Hongjuan; Feng, Qianhua; Zhang, Hongling; Wang, Lei; Zhang, Zhenzhong; Zhang, Yun
Abstract: Spores, the dormant life forms of probiotics, can germinate to metabolically active vegetative cells with the disintegration of their hydrophobic protein coat in the intestinal microenvironment, which provides the possibility for the formation of nanoparticles (NPs) in vivo. Inspired by the natural physiological process of spores, herein, an oral autonomous NPs generator is developed to overcome the spatially variable gastrointestinal tract environment and multibiological barriers. Spores modified with deoxycholic acid (DA) and loaded with chemotherapeutic drugs (doxorubicin and sorafenib, DOX/SOR) serve as an autonomous production line of NPs, which can efficaciously protect the drugs passing through the rugged environment of the stomach and furthermore can be transported to the intestinal environment and colonized rapidly. Subsequently, the DOX/SOR/Spore‐DA NPs are produced by the autonomous NPs generator in the intestinal regions based on the disintegrated hydrophobic protein and the hydrophilic DA, and they can efficiently penetrate the epithelial cells via the bile acid pathway, increasing basolateral drug release. In vitro and in vivo studies confirm that this biological nanogenerator can autonomously produce substantial NPs in the intestine, providing a promising strategy for cancer therapy. Abstract : Inspired by the natural physiological process of spores, a probiotic spore‐based oral autonomous nanoparticles generator is developed for cancer therapy. This smart generator can not only germinate and colonize in the intestine but also form nanoparticles in the intestinal environment, enhancing the stability of drugs in the gastrointestinal tract, and overcome the multibiological barriers of the intestinal epithelium.